"Will they be good enough parents?": Ethical dilemmas, views, and decisions among assisted reproductive technology (ART) providers. Issue 4 (2nd October 2017) - Klitzman, Robert
ABSTRACT: Background : Many adults may make less-than-ideal parents, but important ethical questions arise concerning whether assisted reproductive technology (ART) providers should thus ever refuse treatment to certain patients, and if so, when, and how to decide.Methods : In-depth interviews of approximately 1 hour each were conducted with 27 ART providers (17 physicians, and 10 other health providers).Results : Clinicians often struggle with whether to attempt to assess and predict patients' potential future parenting abilities, and if so, how, and how to proceed if doubts arise. Providers face profound ethical tensions between adults' rights to reproduce and best interests of the eventual children (i.e., to be born into "stable" homes), and questions about the extent of professional responsibilities toward potential parents versus toward future offspring. Providers generally feel uncomfortable with this role, and hence don't want it, partly since they lack training for it, but also because of inherent empirical and ethical uncertainties. Concerns about discrimination based on the mere presence or history of certain diagnoses or traits (e.g., single marital status or past depression) also arise. Clinicians frequently seek to resolve these tensions through various strategies—for example, referring these decisions to others; hoping that patients drop out of treatment; assessing and increasing social support (e.g., arranging for possible co-parents); assisting the patient psychotherapeutically; or seeking to communicate concerns to patients only indirectly or implicitly. Clinics vary in how they make and approach these decisions—whether they rely on a formal ethics or other committee.Conclusions : These data, the first to explore several critical aspects of in vitro fertilization (IVF) providers' views and decision making about assessing the quality of patients' potential future parenting, have critical implications for future practice, education, research, and guidelines. Further empirical and normative scholarship and guidelines are needed to help clarify expectations, processes, and possible approaches to aid providers and patients.